Sarcopenia is an independent risk factor for all-cause mortality rate in patients with diabetic foot ulcers - Yang, Qin; Ni, Xia; Zhang, Yingxiao; Zhu, Baozhen; Zeng, Qinglian; Yang, Chan; Shi, Jiale; Zhang, Chunlin; Cai, Jiahui; Hu, Jinbo; Li, Qifu; Jiang, Yingsong; et al. (Frontiers in Nutrition, 2023)
Objective: This study aimed to determine whether sarcopenia affects the all-cause mortality rate of patients with diabetic foot ulcers (DFUs).Research design and methods: The clinic-based observational study included 217 patients treated at the Department of Endocrinology, the First Affiliated Hospital of Chongqing Medical University during a 4-year period. All subjects underwent dual-energy X-ray absorptiometry to determine their body composition during hospitalization. Diagnosis of sarcopenia was based on the Baumgartner diagnostic criteria. Patients were followed up regularly by phone calls until April 1, 2019, and their survival status was recorded. Univariate and multivariate Cox risk ratio regression models were used to analyze factors influencing the all-cause mortality rate of patients with DFUs. Results :Of the 217 patients, 158 people survived (82.7\%), 33 died (17.3\%), and 26 were lost to follow-up. The median follow-up time was 23 (Range 11-34) months. The majority of patients were male (68.6\%), with a mean age of 67.29±11.14 years. The 5-year survival rate was 68.3\% and 45.9\% for all study patients ($n=217$) and sarcopenia patients ($n=81$), respectively. Multivariate Cox risk regression model showed that age (HR 1.042[95\%CI:1.006, 1.078], $P=0.021$), sarcopenia (HR 5.051[95\%CI:1.968, 12.961], $P=0.001$), and serum creatinine (HR 1.007[95\%CI: 1.003, 1.010], $P<0.001$) were independent risk factors for all-cause mortality rate of patients with DFUs. Kaplan-Meier survival curve indicated that the survival rate of patients with sarcopenia was significantly lower than non-sarcopenia patients($P<0.001$). Conclusions: Sarcopenia is an independent risk factor for all-cause mortality of patients with DFUs and hence an important prognostic factor for patients with DFUs. Active prevention and improvement of sarcopenia can potentially improve the survival outcomes of this patient population.